Learning ready-made items to master new languages. (Open Herald: Periodical of Methodical Research, 2025)
Teaching ready-made language items is an important part of language learning, especially for using them in speaking and writing. This research looks at different methods of helping students remember new vocabulary. Learning groups of words related to a specific topic is seen as an important part of understanding and using new phrases. The article explores several modern approaches to teaching lexical itemsand explains how these methods are used in speaking and writing tasks. It also shows how different learner abilities and factors can affect how well these methods work. These teaching methods can be applied in schools and universities. The article describes the main features of teaching lexical itemsthrough different techniques and explains the scientific principles behind these methods in the learning process.